Evaluation of work plan implementation of community forest management business license case study in Karya Lestari farmers group, Sibaganding Village, Girsang Sipangan Bolon Sub-district, Simalungun Regency. Issue 1 (November 2021) - Sitanggang, Rio Frenky; Rahmawaty; Zaitunah, A
Abstract: One of the Social Forestry schemes is the Community Forest (CF) which aims to empower communities around forest areas. CF Management Business Permits are given to the community through Farmers Groups and are obliged to make a Business Work Plan for a period of 10 years and an Annual Work Plan. The purpose of the study was to evaluate the implementation of the Annual Work Plan for Community Forest management in the Karya Lestari Farmer's Group, Sibaganding Village, Girsang Sipangan Bolon District, Simalungun Regency, based on technical, socio-economic and institutional aspects. The research was carried out between October 2020 and January 2021. The data used are primary and secondary data with the method of taking the object of research by census. Data were analyzed using reduction method, presentation, verification and drawing conclusions. The results showed that the implementation of the Annual Work Plan in 2019 FG Karya Lestari was in 4 activities (14.29 %) and 24 activities (85.71 %). The four activities can be carried out because of the assistance from the local Forest Management Unit, the activities do not require funds and can be carried out in mutual cooperation. The cause of the other activities has not been carried out due to inadequate facilities and infrastructure, lack of funds and low human resources.